History and current perspectives on the biological effects of high-dose spatial fractionation and high dose-rate approaches: GRID, Microbeam & FLASH radiotherapy - Griffin, Robert J (Br J Radiol, 2020)
The effects of various forms of ionising radiation are known to be mediated by interactions with cellular and molecular targets in irradiated and in some cases non-targeted tissue volumes. Despite major advances in advanced conformal delivery techniques, the probability of normal tissue complication (NTCP) remains the major dose-limiting factor in escalating total dose delivered during treatment. Potential strategies that have shown promise as novel delivery methods in achieving effective tumour control whilst sparing organs at risk involve the modulation of critical dose delivery parameters. This has led to the development of techniques using high dose spatial fractionation (GRID) and ultra-high dose rate (FLASH) which have translated to the clinic. The current review discusses the historical development and biological basis of GRID, microbeam and FLASH radiotherapy as advanced delivery modalities that have major potential for widespread implementation in the clinic in future years.